2017
DOI: 10.1371/journal.pone.0181978
|View full text |Cite
|
Sign up to set email alerts
|

Short-term sleep deprivation leads to decreased systemic redox metabolites and altered epigenetic status

Abstract: Sleep is critical for repair as well as the rejuvenation processes in the body and many of these functions are regulated via underlying cellular metabolic homeostasis. Changes in sleep pattern are reported to alter such metabolic function resulting in altered disease susceptibility or behavior. Here, we measured the extent to which overnight total sleep deprivation (SD) in young adult humans can influence systemic (plasma-derived) redox-metabolism including the major antioxidant, glutathione as well as DNA met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 38 publications
2
43
0
2
Order By: Relevance
“…Free radicals are postulated to accumulate during awakening, inter alia, due to enhanced metabolic activity, and are claimed to be responsible for the unfavorable effects of sleep deprivation [ 32 , 33 ]. During sleep deprivation, the ability to perform tasks that require additional energy expenditure may be impaired [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Free radicals are postulated to accumulate during awakening, inter alia, due to enhanced metabolic activity, and are claimed to be responsible for the unfavorable effects of sleep deprivation [ 32 , 33 ]. During sleep deprivation, the ability to perform tasks that require additional energy expenditure may be impaired [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…One route by which sleep deprivation could impact adult DG neurogenesis and thereby affect hippocampal function is through epigenetic modifications. Both acute and chronic sleep deprivation produce broad changes in epigenetic markers and patterns of gene transcription in rodents and humans . Of particular interest, depriving mice of sleep for 3 days downregulates hippocampal CBP expression, reduces hippocampal histone acetylation levels at Bdnf promoter regions, and weakens spatial memory , suggesting that sleep deprivation can impair cognition by disrupting hippocampal BDNF signaling, which is important for the maturation and growth of adult‐born DG neurons .…”
Section: Role Of Sleep In Epigenetic Regulation Of Adult Dg Neurogenesismentioning
confidence: 99%
“…However, some studies show effects of TSD that could not be considered as neuroprotective; for example, Trivedi et al [116] found that glutathione, ATP, cysteine, and homocysteine levels in plasma were significantly reduced as a result of one night of TSD, while Meier-Ewert et al [117] reported that one night of TSD increased serum C reactive protein concentrations. Also, one night of TSD causes an increase of serum concentration of interleukin 6 (IL-6), a proinflammatory cytokine in depressive patients as in healthy subjects; but in healthy individuals sleep rebound increased the level of interleukin-1-receptor antagonist (IL-1RA) [118], which inhibits the action of the proinflammatory interleukins 1alpha and 1beta.…”
Section: Sleep Deprivation In Humansmentioning
confidence: 99%